A comparative review of microplastics and nanoplastics: Toxicity hazards on digestive, reproductive and nervous system - Yin, Kai; Wang, Yu; Zhao, Hongjing; Wang, Dongxu; Guo, Menghao; Mu, Mengyao; Liu, Yachen; Nie, Xiaopan; Li, Baoying; Li, Jingyan; Xing, Mingwei (The Science of the total environment, 2021)
Due to its excellent physical and chemical properties and low price, plastic has replaced part of the use of stone, wood and metal. The inability to degrade and improper handling have caused plastic pollution to become one of the most serious environmental problems in the world today. Plastic fragments undergo ultraviolet radiation, natural weathering, and biodegradation to form microplastics (MPs) and nanoplastics (NPs)11In this review, MPs stands for micro-scale microplastics; NPs stands for nano-scale microplastics; Microplastic stands for microplastics of all sizes.. The current research on MPs mainly focuses on transportation, bioaccumulation and toxicity. However, existing reviews treat NPs and MPs as a whole to discuss toxic damage, and ignore their differences in toxicity. In this review, we provided the latest research information on the differences in toxicity between MPs and NPs in the digestive system, reproductive system and nervous system, and explored the possible reasons for differences in toxicity for the first time. Finally, it is recommended to consider the influence of microplastics components on the differences in toxicity, as most of the researches now focuses on a few types of microplastics. And it is necessary to study the unique toxicity mechanism of MPs/NPs in bioaccumulation and pathway activation from the differences in physical properties. [Display omitted] •Compare the toxicity hazards of microplastics/nanoplastics (MPs/NPs) among digestive, reproductive and nervous systems.•In intestine, NPs cause higher inflammation and oxidative stress, and MPs cause more serious intestinal flora disorders.•In liver, MPs produce higher oxidative stress and lipid metabolism disorders.•NPs cause higher reproductive toxicity and neurotoxicity than MPs.